Patient and Clinician Satisfaction With Diabetes Group Visits in Community Health Centers - Samantha E Mannion MD (SAGE Publishing, 2021)
Diabetes group visits (GVs) have been shown to improve glycemic control and quality of care. However, little is known about the patient and clinician experience. We trained staff to conduct a 6-month GV intervention at six community health centers (CHCs) for adults with uncontrolled diabetes. Patient satisfaction was analyzed using postintervention surveys. Clinician satisfaction was analyzed through pre and posttraining surveys and 1:1 semistructured interviews. Twenty-seven staff and clinicians were trained. Fifty-one adult patients were enrolled and 90% reported high satisfaction with the program. Patients enjoyed longer visits with peer support and felt better equipped to manage barriers to diabetes control. 88% of staff reported that they enjoyed taking part in the program and noted improved team morale, professional development, and increased interdisciplinary collaboration. Perceived challenges of GVs included time investment for a new program, integration into workflow, and staff turnover. Patient and staff satisfaction was high across multiple domains. Staff noted many benefits but reported challenges with patient recruitment and retention as well as the time needed to implement GVs.